Evaluation and Empirical Analysis of Competitiveness of the Sports Industry Based on the Theory of Competitive Advantage - Yingmin Cui (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The examination of the competitiveness of the sports industry in a region enables policymakers to comprehend the competitiveness of the sports industry in an area's current growth level and identify sports industry issues. However, previous research has prioritized the sports business's development stage over the competitiveness indices' selection and measurement. This study attempts to evaluate and experimentally examine the competitiveness of the sports sector based on the theory of competitive advantage to solve the problem. In particular, the sports industry comprises ten subindustries: the lottery industry, sports tourism, venue industry, competitive performance industry, fitness and entertainment industry, sales industry, sports product manufacturing, training industry, intermediary industry, and media industry. Then, numerous industrial clusters for manufacturing sports products and industrial programs for sports tourism were provided. Next, an evaluation index system (EIS) for the competitiveness of the sports sector was devised, and the meaning of each index was clarified. The writers then described how to evaluate the competitiveness of the sports business and its impacting elements. Various tests were conducted to demonstrate the scientific nature of the EIS and provide empirical, analytical results.